Utility of Lead aVR for Identifying the Culprit Lesion in Acute Myocardial Infarction - Kühl, Jørgen Tobias (Ann Noninvasive Electrocardiol, 2009)
Background: Lead aVR is a neglected, however, potentially useful tool in electrocardiography. Our aim was to evaluate its value in clinical practice, by reviewing existing literature regarding its utility for identifying the culprit lesion in acute myocardial infarction (AMI). Methods: Based on a systematic search strategy, 16 studies were assessed with the intent to pool data; diagnostic test rates were calculated as key results. Results: Five studies investigated if ST‐segment elevation (STE) in aVR is valuable for the diagnosis of left main stem stenosis (LMS) in non–ST‐segment AMI (NSTEMI). The studies were too heterogeneous to pool, but the individual studies all showed that STE in aVR has a high negative predictive value (NPV) for LMS. Six studies evaluated if STE in aVR is valuable for distinguishing proximal from distal lesions in the left anterior descending artery (LAD) in anterior ST‐segment elevation AMI (STEMI). Pooled data showed a sensitivity of 47%, a specificity of 96%, a positive predicative value (PPV) of 91% and a NPV of 69%. Five studies examined if ST‐segment depression (STD) in lead aVR is valuable for discerning lesions in the circumflex artery from those in the right coronary artery in inferior STEMI. Pooled data showed a sensitivity of 37%, a specificity of 86%, a PPV of 42%, and an NPV of 83%. Conclusion: The absence of aVR STE appears to exclude LMS as the underlying cause in NSTEMI; in the context of anterior STEMI, its presence indicates a culprit lesion in the proximal segment of LAD.